COVID-19-induced hair shedding and related risk factors: A Saudi perspective - Abrar E. Bukhari; Dalal A. AlDosari; Manal A. AlDosari; Reema F. Muqrin; Othillah M. Moazin; Malak M. Almutlq; Saad M. Altalhab; Ruaa S. Alharithy; Abdullah I. Alkhalifah (Journal of Family Medicine and Primary Care)
Introduction: Many cases of telogen effluvium (TE), acute hair shedding, following coronavirus disease 2019 (COVID-19) were reported during the pandemic. Methodology: We conducted a cross-sectional study to assess the relationship between COVID-19 and TE in Saudi Arabia. Self-administered online questionnaires were distributed online between March and September 2022 in Saudi Arabia. A multivariate logistic regression model was used to determine risk factors associated with TE post-COVID-19 (significance at P < 0.05). Results: Of the 703 responders, 392 were included in the study. 59.70% (n = 234) recognized hair shedding during or after COVID-19. The time taken to realize hair shedding (3 or 6 months) and the duration varied (3, 6, >6 months). The risk factors significantly related to TE post-COVID-19 were: female sex (P < 0.001, odds ratio [OR] = 2.98), COVID-19 antiviral treatment (P = 0.032, OR = 3.02), and TE history (P = 0.001, OR = 3.78). Conclusion: Healthcare providers and physicians should be aware of the relationship between TE and COVID-19, to easily recognize, treat, and improve their patients' outcomes).